Implementation of an Allergic Reaction Reporting Tool for School Health Personnel: A Pilot Study of Three Chicago Schools. (October 2019) - Aktas, Ozge N.; Kao, Lauren M.; Hoyt, Alice; Siracusa, Mary; Maloney, Rebekah; Gupta, Ruchi S.
Food allergy (FA) impacts 8% of U.S. children, thus it is critical to document allergic reactions to assist schools in managing FAs. We implemented and evaluated an online tool to assist school health personnel in tracking the characteristics of allergic reactions occurring at schools. The Online School Allergic Reaction Registry (OScARR) was modified from the Epinephrine Administration Form developed by the Massachusetts Department of Public Health, adapted for integration into existing school health records, and implemented in three Chicago schools during the 2016–2017 school year. All allergic reactions occurring at participating schools were recorded by school nurses. Twenty-five percent of the 20 allergic reactions reported were characterized as anaphylaxis by school nurses. School nurses reported that they would recommend OScARR for use in other schools. Detailed data obtained from three Chicago schools underscore the importance of proper documentation to improve the understanding of the causative allergen and location and management of allergic reactions in schools.